Food security and sustainable agriculture. Issue 1 (April 2020) - Ala, A; Ridwan, I
Abstract: Responding to the increase of the world population, food availability in developing countries will need to increase, 60% by 2030 and double by 2050. These figures are equivalent to 42% and 70% growth in global food production, respectively. Many Indonesian lived in poor rural areas especially children still experience malnourished, underweight and suffer from stunted growth. This paper discusses food security issues from the perspective of sustainable agriculture, its challenges and policies supporting the efforts to sustain food security. The paper also compares the food security concept with food sovereignty related to the production aspect and the sustainability of the supply chain and accessibility of the food.